EFFECTIVENESS OF SCIENCE CARD GAME ON EXCRETION SYSTEM TO HUMAN MATERIALS TO IMPROVE STUDENT COGNITIVE LEARNING OUTCOMES - Prastiwi Aristya Chonita; Wahono Widodo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
This study aims to describe the effectiveness of the Science card game to improve student learning outcomes. This type of research is the development using the Research and Development (R&D) model. The research design used was a one-group pretest-posttest design conducted on 32 students of class VIII-F of SMPN 50 Surabaya. The results of the effectiveness study were reviewed through two aspects: student learning outcomes and student questionnaire responses. Student learning outcomes can be reviewed from the results of the pretest and posttest. Obtained the average results of student pretest of 50.00 and the average posttest results of 84.79. Obtained an increase of 100% with details of 62.50% of students or as many as 20 students get an increase with a moderate category, and 37.50% or as many as 12 students get an increase in the high category. The average N-gain score was 0.68 in the medium category. Then the results of student responses showed an average of